Amitav Ghosh, The Great Derangement: Climate Change and the Unthinkable - Shapiro, Arthur M. (Journal for the Study of Religion, Nature and Culture, 2018)
Amitav Ghosh, The Great Derangement: Climate Change and the Unthinkable (Chicago and London: University of Chicago Press, 2016), 196 pp., $22.00 (cloth), ISBN: 978-0-226-32303-9.